Independence and Impartiality of Judges, Prosecutors and Lawyers - UN - Office of the High Commissioner for Refugees (My University, 2016)
Reseña:This chapter will deal with two of the fundamental pillars of a democraticsociety respectful of the rule of law and the effective protection of human rights,namely, the independence and impartiality of the judiciary and prosecutors, andthe independence of lawyers. It will first describe the role played by judges,prosecutors and lawyers in this regard; and secondly, will focus on the various legallimitations on, and de facto threats to, the ability of judges, prosecutors and lawyers toexercise their professional responsibilities in an independent and impartial manner.Finally, this chapter will analyse the existing international legal standards relating to thefunctioning of the legal professions and selected relevant case-law.This chapter will deal with two of the fundamental pillars of a democratic society respectful of the rule of law and the effective protection of human rights, namely, the independence and impartiality of the judiciary and prosecutors, and the independence of lawyers. It will first describe the role played by judges, prosecutors and lawyers in this regard; and secondly, will focus on the various legal limitations on, and de facto threats to, the ability of judges, prosecutors and lawyers to exercise their professional responsibilities in an independent and impartial manner. Finally, this chapter will analyse the existing international legal standards relating to the functioning of the legal professions and selected relevant case-law.